Reproductive Health Governance: Availability and Professional Use of Misoprostol in Benin and Burkina Faso - Seydou Drabo; Fatoumata Ouattara; Carine Baxerres; Agnès Guillaume (Nordic Journal of African Studies, 2022)
Misoprostol is effective not only for gastroenterology indications but also for reproductive health-related conditions and for the reduction of maternal mortality. The use of misoprostol is well documented in Latin America, where it is widely used for abortions. However, scant knowledge exists regarding its use in African contexts. In this study, we describe and analyse the conditions of the professional use of misoprostol in Benin and Burkina Faso. We ask the following questions: How accepted is misoprostol in Benin and Burkina Faso? What was the process leading to the official recognition of misoprostol in both countries? Which actors were involved in this process? How do health care workers perceive and use misoprostol in the context of care? Theoretically, we use the concepts ‘social life of medicine’ and ‘reproductive governance’ to analyse the position of misoprostol within the broader system of health policy, as well as its professional usage within the health care system. The fieldwork conducted in Benin and Burkina Faso highlights the conditions of the institutional acceptability of the drug and the logics underlying the use and non-use of misoprostol by health workers in both countries. The article highlights the social life of misoprostol by showing how the governance surrounding its use contributes to the development and cultivation of suspicions towards the drug among health care providers and institutional actors – suspicions that consequently restrict the availability of misoprostol as a medical therapeutic option.